Self-care of Nursing Students in Health Promotion (International Journal of Psychosocial Rehabilitation, 2020)
The research arises from the diagnosis of a group of teachers who detected the need in the health promotion activity to give special emphasis to self-care in students. The objective of the study was to establish self-care strategies in promoting health in nursing students. This is a descriptive-analytical, longitudinal study carried out in the period May-October 2018 in the Nursing degree, Faculty of Health Sciences of the State University of the South of Manabí, in Ecuador. Concluding that self-care and health promotion are found in the undergraduate health education standards of the most influential regulators. The categories of social interaction, personal wellbeing, and risk prevention show the level of self-care that nursing students have and give guidelines on the indicators that should be strengthened in their training.